Climatic Alternate Wetting and Drying (AWD) suitability maps for Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The GIS-based maps have been developed and adjusted after stakeholder consultation. The have been advocated in several national and international workshops and a scientific publication is being prepared.